Penerapan Proyek Penguatan Profil Pelajar Pancasila di TK Dharma Wanita Kencong Berdasarkan Modul P5 - Ade Irma Noviyanti (Journal of Elementary School (JOES), 2023)
The Structure of the Independent Curriculum in Early Childhood Education (PAUD) consists of Intracurricular Learning Activities and Projects to Strengthen Pancasila Student Profiles (P5). Intra-curricular learning activities are designed so that students can achieve the competencies listed in the learning outcomes (CP), while the Pancasila student profile strengthening project aims to strengthen efforts to achieve Pancasila student profiles that refer to the Standard Level of Child Development Achievement for PAUD. The purpose of this study was to determine the implementation of the Pancasila Student Profile Strengthening Project at Dharma Wanita Kindergarten in Kencong District, Jember Regency. The research method uses a descriptive narrative with a case study approach. The results showed that the implementation of the Pancasila Student Profile Strengthening Project in Dharma Wanita Kindergarten had gone well. Keywords: analysis, application, project to strengthen the profile of Pancasila students